Neuroprotection Mediated by P2Y(13) Nucleotide Receptors in Neurons - Pérez-Sen, Raquel (Comput Struct Biotechnol J, 2015)
ADP-specific P2Y(13) receptor constitutes one of the most recently identified nucleotide receptor and the understanding of their physiological role is currently under investigation. Cerebellar astrocytes and granule neurons provide excellent models to study P2Y(13) expression and function since the first identification of ADP-evoked calcium responses not attributable to the related P2Y(1) receptor was performed in these cell populations. In this regard, all responses induced by ADP analogues in astrocytes resulted to be Gi-coupled activities mediated by P2Y(13) instead of P2Y(1) receptors. Similarly, both glycogen synthase kinase-3 (GSK3) and ERK1/2 signaling triggered by 2MeSADP in cerebellar granule neurons were also dependent on Gi-coupled receptors, and mediated by PI3K activity. In granule neurons, P2Y(13) receptor was specifically coupled to the main neuronal survival PI3K/Akt-cascade targeting GSK3 phosphorylation. GSK3 inhibition led to nuclear translocation of transcriptional targets, including β-catenin and Nrf2. The activation of the Nrf2/heme oxygenase-1 (HO-1) axis was responsible for the prosurvival effect against oxidative stress. In addition, P2Y(13)-mediated ERK1/2 signaling in granule neurons also triggered activation of transcription factors, such as CREB, which underlined the antiapoptotic action against glutamate-induced excitotoxicity. Finally, a novel signaling mechanism has been recently described for a P2Y(13) receptor in granule neurons that involved the expression of a dual protein phosphatase, DUSP2. This activity contributed to regulate MAPK activation after genotoxic stress. In conclusion, P2Y(13) receptors harbored in cerebellar astrocytes and granule neurons exhibit specific signaling properties that link them to specialized functions at the level of neuroprotection and trophic activity in both cerebellar cell populations.